Four-armed Indra placed inside a devakostha-niche - Temples of India Project Team (Jio Institute, 2024)
A four-armed Indra placed inside a devakostha-niche, easily identifiable by his vahana, an elephant. The loose architectural fragment from Harsha Hill is now housed in the Government Museum, Sikar. Although the two hands on the left side are broken, the upper right holds an ankush and the lower one gracefully rests on his right leg.